Versatile and cost-efficient cleanup of viscous crude oil by an elastic carbon sorbent from direct pyrolysis of a melamine foam. Issue 18 (27th April 2021) - Niu, Haifeng; Li, Jianbo; Qiang, Zhe; Ren, Jie
Abstract : Carbon sponge with photothermal and Joule thermal properties was prepared by pyrolysis of melamine sponge. The significantly decreased viscosity of crude oil from heating enables a rapid and continuous crude oil cleanup under all weather conditions. Abstract : Rational sorbent technology for crude oil cleanup requires the capability of rapid uptake and a low-cost and simple processing method for large-scale manufacturing. Herein, an elastic carbon sorbent can be fabricated through the direct pyrolysis of a melamine foam at 1000 °C for 2 h. The carbonized melamine foam (CMF) is light weight (density: 5.4 mg cm −3 ; porosity > 97.2%), superhydrophobic (water contact angle: 151 ± 2°), mechanically robust (complete recovery after 80% strain deformation) and highly efficient in crude oil uptake (148.7 g g −1 crude oil at 60 °C). More importantly, the CMF has excellent photo- and Joule-thermal conversion efficiency for significantly reducing the viscosity of heavy crude oil under mild sunlight exposure or a relatively low voltage. These advantages enable CMFs to provide a fast cleanup approach for accidental oil spills under all weather conditions. Continuous oil recovery has also been demonstrated by using a piece of heated CMF and a vacuum pump. Overall, the CMF offers an ideal material solution for addressing large-scale crude oil cleanup through its versatile and efficient cleanup approaches.